Neuropsychological evidence for case-specific reading: multi-letter units in visual word recognition. - Hall, D; Humphreys, G; Cooper, A (2001)
We describe a patient (GK) who shows symptoms associated with Balint's syndrome and attentional dyslexia. GK was able to read words, but not nonwords. He also made many misidentification and mislocation errors when reporting letters in words, suggesting that his word-naming ability did not depend upon preserved position-coded, letter identification. We show that GK was able to read lower-case words better than upper-case words, but upper-case abbreviations better than lower-case abbreviations. Spacing the letters in abbreviations disrupted identification, as did mixing the case of letters within words. These data cannot be explained in terms of letter-based reading or preserved holistic word recognition. We propose that GK was sensitive to the visual familiarity of adjacent letter forms.